2000
DOI: 10.1017/s0959270900000265
|View full text |Cite
|
Sign up to set email alerts
|

Local knowledge of the Bornean Peacock-pheasant Polyplectron schleiermacheri: a critique of O'Brien et al. (1998a)

Abstract: In a recent study, O'Brien et al. (1998a) sought to provide a better understanding of the distribution and status of the Bornean Peacock-pheasant Polyplectron schleiermacheri in Central Kalimantan, Indonesia, based on an analysis of questionnaires and semi-structured interviews with local inhabitants. This was the first scientific contribution concerning this species after the launch of the Conservation Action Plan for Pheasants (McGowan and Garson 1995). Although the authors of this study acknowledged and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Long & Collar (2002), on the basis of tallying the number of records in different habitat types and/or on the basis of locality names, cautiously inferred 'a close ecological link [of Bornean ground-cuckoo] with riverine fringes and flood plains throughout the island'. O'Brien et al (1998) made inferences about the habitat preferences of the Bornean peacock-pheasant based on data from interviews (for a critique, see Sözer et al 2000 and, and concluded that the species has a preference for primary lowland forest, avoiding swamp and riverine forest. Finally, Collar et al (2001), again on the basis of tallying records of this species, suspected the Bornean peacock-pheasant to be a bird of the lowland dipterocarp and alluvial forest, with a possible preference for black, more fertile (alluvial) soils.…”
Section: Discussionmentioning
confidence: 99%
“…Long & Collar (2002), on the basis of tallying the number of records in different habitat types and/or on the basis of locality names, cautiously inferred 'a close ecological link [of Bornean ground-cuckoo] with riverine fringes and flood plains throughout the island'. O'Brien et al (1998) made inferences about the habitat preferences of the Bornean peacock-pheasant based on data from interviews (for a critique, see Sözer et al 2000 and, and concluded that the species has a preference for primary lowland forest, avoiding swamp and riverine forest. Finally, Collar et al (2001), again on the basis of tallying records of this species, suspected the Bornean peacock-pheasant to be a bird of the lowland dipterocarp and alluvial forest, with a possible preference for black, more fertile (alluvial) soils.…”
Section: Discussionmentioning
confidence: 99%